ДАРАҚТ (АҒАШ) ӨСИМЛИГИ МЕНЕН БАЙЛАНЫСЛЫ МИФОЛОГИЯЛЫҚ ОЙЛАЎЛАР ҲАҚҚЫНДА (өзбек, қарақалпақ ҳәм инглис фольклоры мысалында) - Сапарниязов, Р. (FAN va JAMIYAT, 2021)
This article deals with the significance of concepts in a comparative way connected with spiritual wealth of our nation, deep sources of concepts and beliefs, interrelationship of man with plants, trees and bushes as totem symbols in the examples of the Uzbek, Karakalpak and English folklore.